Video observation during R/V Heincke cruise HE474 in the German Bight with link to raw data files - H Christian Hass; Svenja Papenmeier (PANGAEA, 2019)
At 25 stations in the German Bitght underwater videos were recorded with Kongsberg Color Zoom Camera and GOPRO 3+ Black Edition to ground truth sidescan sonar backscatter data. The R/V Heincke was drifting while data acquisition.